Gallbladder agenesis, a diagnostic difficulty - Thulasilingam, Kathirazhagan; Akhter, Jameel (International Surgery Journal, 2022)
Gallbladder agenesis is a very rare presentation where surgeons were put in a situation to diagnose the same during laparoscopy for cholecystectomy or during diagnostic laparoscopy. The preoperative diagnosis of gallbladder agenesis remains a challenge to both surgeons and radiologists. Here we present a case of gall bladder agenesis in a 59-year-old male with a preoperative diagnosis of a contracted gallbladder. Agenesis was confirmed after diagnostic laparoscopy and MRCP.